Effect of acetabular cup design on metal ion release in two designs of metal‐on‐metal hip resurfacing. Issue 7 (24th June 2014) - Cadossi, Matteo; Tedesco, Giuseppe; Savarino, Lucia; Baldini, Nicola; Mazzotti, Antonio; Greco, Michelina; Giannini, Sandro
Abstract The purpose of this observational prospective cohort study was to evaluate the serum concentrations of cobalt (Co), chromium (Cr), and nickel (Ni) at a 2‐year follow‐up in patients operated on with a novel design of hip resurfacing: Romax resurfacing system (RRS). RRS is characterized by the presence of an acetabular notch which theoretically provides a wider range of motion and a reduced incidence of groin pain. The presence of radiolucencies and functional outcome, assessed using the Harris hip score (HHS) and the University of California Activity scale (UCLA), were secondary endpoints. Moreover, these results were compared with those obtained in our previous study from a similar cohort of patients implanted using the Birmingham Hip Resurfacing (BHR) system. At a 2‐year follow‐up, the serum levels of Co in patients operated on using the RRS were five times higher (p = 0.0002) than those found before surgery (Co, means: 1.04 and 0.20 ng/mL, respectively); similarly, Cr levels were 13 times higher (p < 0.0001) at a 2‐year follow‐up than before surgery (Cr, means: 1.69 and 0.13 ng/mL, respectively). Ni concentrations (0.42 and 0.78 ng/mL) were not significantly different (p = 0.16), even if they increased 86% after surgery. In the RRS patients, an inverse correlation was found between Co and Cr concentrations and length of follow‐up (Co: r = −0.64, p = 0.0096; Cr: r= −0.45, p = 0.08). The serum levels of Co and Cr were not significantly different between RRS (Co: 1.04 ng/mL and Cr: 1.69 ng/mL) and BHR (Co: 1.39 ng/mL and Cr: 2.30 ng/mL) patients at 2 years (p = 0.95 and 0.26 for Co and Cr, respectively). Our results showed that RRS patients achieved an excellent clinical outcome with limited metal ion release. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 102B: 1595–1601, 2014.